2018
DOI: 10.1002/eap.1724
|View full text |Cite
|
Sign up to set email alerts
|

Current and projected cumulative impacts of fire, drought, and insects on timber volumes across Canada

Abstract: Canada's forests are shaped by disturbances such as fire, insect outbreaks, and droughts that often overlap in time and space. The resulting cumulative disturbance risks and potential impacts on forests are generally not well accounted for by models used to predict future impacts of disturbances on forest. This study aims at projecting future cumulative effects of four main natural disturbances, fire, mountain pine beetle, spruce budworm and drought, on timber volumes across Canada's forests using an approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 85 publications
0
47
2
Order By: Relevance
“…Second, higher phylogenetic dissimilarity may buffer trees against the negative effects of specialist pest and pathogen outbreaks (Parker et al 2015;Grossman et al 2018). Studies have suggested that outbreaks of pests such as spruce budworm have increased in intensity in our study region (Boucher et al 2018) and regions previously inaccessible to the pest due to cold temperatures will become more susceptible as the climate warms (Pureswaran et al 2015). Further studies in areas of ongoing pestoutbreak that integrate local neighbourhood diversity and landscape-level diversity are required to determine whether the second mechanism is occurring at ecologically relevant magnitudes.…”
Section: Discussionmentioning
confidence: 82%
“…Second, higher phylogenetic dissimilarity may buffer trees against the negative effects of specialist pest and pathogen outbreaks (Parker et al 2015;Grossman et al 2018). Studies have suggested that outbreaks of pests such as spruce budworm have increased in intensity in our study region (Boucher et al 2018) and regions previously inaccessible to the pest due to cold temperatures will become more susceptible as the climate warms (Pureswaran et al 2015). Further studies in areas of ongoing pestoutbreak that integrate local neighbourhood diversity and landscape-level diversity are required to determine whether the second mechanism is occurring at ecologically relevant magnitudes.…”
Section: Discussionmentioning
confidence: 82%
“…Insect defoliation and pathogen outbreaks might predispose weakened trees to greater vulnerability to treefall under future strong wind episodes (e.g., Taylor and MacLean 2009;Girard et al 2014;Wilson and MacLean 2015). Fire risk can also increase in tree stands previously attacked by insect defoliators (e.g., eastern spruce budworm in the southern Boreal Shield), as the accumulation of dead, vertically arranged wood structures can allow greater potential of surface fires to reach the canopy, resulting in more severe fires (Candau et al 2018; see also Boucher et al 2018).…”
Section: Ecosystem Condition and Productivitymentioning
confidence: 99%
“…In addition, forests will experience altered growing conditions due to rapid increases in temperature and shifting precipitation trends [3,4]. These stressors could result in declining forest health or increasing mortality, and potentially precipitate abrupt shifts in species composition [5][6][7]. To anticipate potential impacts of these stressors on forest ecosystems and develop corresponding adaptation strategies, forestry practitioners are increasingly using climatebased vulnerability assessments [8,9].…”
Section: Introductionmentioning
confidence: 99%